Discourse on the Extended Meaning of Shahada: A Cognitive-Pragmatic Approach - Chaer, Hasanuddin; Sirulhaq, Ahmad; Rasyad, Abdul; Abduracman Malik , Djamil (Journal of Al-Tamaddun, 2024)
The existence of God is an extraordinary occurrence that presents a challenge for the limited human intellect to comprehend. Hence, arriving at that conviction necessitates unwavering trust and belief. In Islam, the affirmation of this conviction must be expressed in two lines known as the shahada. In addition to this paranormal event, the language structure pertaining to the two words found in the shahada includes the term أشهد (ashhadu), which translates as ‘I testify’. This statement assumes that the person testifying had prior knowledge of God’s existence, despite the fact that it is supernatural and challenging to ascertain. Why is the word أشهد (ashhadu) included in both sentences of the shahada? This essay seeks to examine the semantic significance of the linguistic expression realised in the proclamation of the two sentences of the shahada, specifically focusing on the word أشهد (ashhadu). This analysis will be conducted within a cognitive-pragmatic or sociocognitive framework. Typically, the cognitive pragmatics method considers not just the semantic meaning of a statement but also the pragmatic meaning of an utterance. During a speech or communication event, both of these meanings are consistently present as an individual intellectually constructs a representation of the context and scenario. The context encompasses not just tangible objects but also intangible aspects, for instance psychological and cognitive factors, including beliefs and knowledge. The findings obtained by this study indicate that the sentence أشهد (ashhadu), in addition to its semantic meaning of ‘I testify’, also possesses a pragmatic-psychological significance in the form of a linguistic texture (zauqullughoh) that may be experienced by the speaker. This may possibly offer psychological encouragement to individuals when they begin to self-explore or engage with their originator.